(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract- This research study has been done in the forest area near sarudih tea garden in jashpur district Chhattisgarh. This study was conducted from Jun 2019 to Dec 2021. A total of 97 Avian species where recorded in different habitat during the study period. Among the species observed 38 Abundant species, 36 Uncommon species and 23 common Species were observed. At these study site 97 is species were recorded in different habitats and different season. Maximum 65 species diversity recorded in forest area and lowest 14 species in fallow land. The habitat of birds is also affected by the availability of food and season. Forest are the best habitat for birds. But due to human activities, forests and other habitat of birds are rapidly getting destroyed. Due to which the number of birds in decreasing. The highest number of abundant. Avian species were found in forest area. Apart from this, uncommon avian species were found in forest area. This research study provides basic information for studying birds in this area to help conserve their habitats in future.